Cardiovascular effects of SPARK conducted electrical weapon in healthy subjects - Scherr, Carlos; de Carvalho, Antonio Carlos; Belem, Luciano Juaçaba; Loyola, Luiz Henrique; Guerra, Renata Leborato; Blanco, Fernanda; Mangia, Claudio (International journal of cardiology, 2016)
The increasing use of conducted electronic weapons (CEW) cause concern regarding its secure application, specially regarding the implications in the cardiovascular system. The objective was to determine Spark CEW safety through cardiovascular parameters analysis of healthy volunteers subjected to its use. Volunteers over 18years without cardiovascular disease or recent use of illegal drugs were submitted, before and after being affected with Spark CEW, to clinical evaluation; blood collection for serum laboratory tests; transthoracic electrocardiography at rest, transthoracic echodopplercardiogram and 24hour Holter. All 71 patients reported being incapable of any voluntary reaction during the shock of the application time. No arrhythmia or myocardial necrosis was related to the use of non-lethal weapon SPARK. Reported adverse events were self-limited, and mostly mild. SPARK brand CEW is effective in incapacitating individuals by the shock of the application time, without causing.